2002
DOI: 10.1159/000059436
|View full text |Cite
|
Sign up to set email alerts
|

Direct Actions of Estradiol on the Anterior Pituitary Gland Are Required for Hypothalamus-Dependent Lactotrope Proliferation and Secretory Surges of Luteinizing Hormone but Not of Prolactin in Female Rats

Abstract: Estradiol induces surges of prolactin (PRL) and luteinizing hormone (LH) secretion as well as lactotrope proliferation in female rats. We examined whether these hypothalamus-dependent events require the direct action of estradiol on the anterior pituitary gland by selective blockade of its peripheral actions, using ICI182,780 (ICI), an antiestrogen that cannot cross the blood-brain barrier. Injection of ICI into ovariectomized rats, at a dose of 250 µg/day for 4 days, almost completely inhibited estradiol-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 51 publications
2
26
0
3
Order By: Relevance
“…This effect of estradiol could be mediated by modifying cell phenotypic features that increase the responsiveness of the anterior pituitary cells to proapoptotic signals. Also, it has been suggested that the sensitizing action of estradiol is required for lactotrope proliferation at estrus (32). Therefore, estradiol may participate in anterior pituitary cell renewal sensitizing the cells to both mitogenic and apoptotic signals.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of estradiol could be mediated by modifying cell phenotypic features that increase the responsiveness of the anterior pituitary cells to proapoptotic signals. Also, it has been suggested that the sensitizing action of estradiol is required for lactotrope proliferation at estrus (32). Therefore, estradiol may participate in anterior pituitary cell renewal sensitizing the cells to both mitogenic and apoptotic signals.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, discerning whether estrogen amplifies GH secretion via actions on the hypothalamus compared with the pituitary gland remains difficult. Based upon preliminary evidence that E 2 may prolong GH secretory bursts (13), we hypothesized that the estrogen effect is secretagogue selective and depends upon ER␣ pathways outside the brain.To begin to address the question where E 2 acts in vivo, we implemented a tripartite experimental paradigm comprising 1) escalating transdermal E 2 delivery on a schedule known to double GH secretion in postmenopausal women (13); 2) concomitant administration of placebo or a selective ER␣ antagonist [fulvestrant (FUL)] that does not cross the blood-brain barrier (33,46,50); 3) maximally effective stimulation with combined secretagogues that drive GH secretion via GHRP and/or GHRH receptors (12,42,43). The rationale was based on three considerations.…”
mentioning
confidence: 99%
“…To begin to address the question where E 2 acts in vivo, we implemented a tripartite experimental paradigm comprising 1) escalating transdermal E 2 delivery on a schedule known to double GH secretion in postmenopausal women (13); 2) concomitant administration of placebo or a selective ER␣ antagonist [fulvestrant (FUL)] that does not cross the blood-brain barrier (33,46,50); 3) maximally effective stimulation with combined secretagogues that drive GH secretion via GHRP and/or GHRH receptors (12,42,43). The rationale was based on three considerations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Μία πρόσφατη µελέτη σε επίµεις έδειξε, ότι η απευθείας δράση της Ε2 στον πρόσθιο λοβό της υπόφυσης είναι υποχρεωτική για τη δράση της θετικής παλλίνδροµης ρύθµισης (positive feedback) στην έκκριση της LH (Yin et al, 2002). Η προγεστερόνη φαίνεται επίσης να ασκεί θετική παλλίνδροµη ρύθµιση (positive feedback) µέσω του υποθαλάµου (Terasawa et al, 1982).…”
Section: η έναρξη του κύµατος της Lhunclassified